Mast cells contribute to the resolution of allergic inflammation by releasing resolvin D1 - Pier Giorgio Puzzovio; Hadas Pahima; Tresa George; David Mankuta; Ron Eliashar; Ekaterini Tiligada; Bruce D. Levy; Francesca Levi-Schaffer (Elsevier, 2023)
Background: Mast cells are initiators and main effectors of allergic inflammation, together with eosinophils, with whom they can interact in a physical and soluble cross-talk with marked pro-inflammatory features, the Allergic Effector Unit. The pro-resolution role of mast cells, alone or in co-culture with eosinophils, has not been characterized yet. Objectives: We aimed to investigate select pro-resolution pathways in mast cells in vitro and in vivo in allergic inflammation. Methods: In vitro, we employed human and murine mast cells and analyzed release of resolvin D1 and expression of 15-lipoxygenase after IgE-mediated activation. We performed co-culture of IgE-activated mast cells with peripheral blood eosinophils and investigated 15-lipoxygenase expression and Resolvin D1 release. In vivo, we performed Ovalbumin/Alum and Ovalbumin/S. aureus enterotoxin B allergic peritonitis model in Wild Type mice following a MC "overshoot" protocol. Results: We found that IgE-activated mast cells release significant amounts of resolvin D1 30 min after activation, while 15-lipoxygenase expression remained unchanged. Resolvin D1 release was found to be decreased in IgE-activated mast cells co-cultured with peripheral blood eosinophils for 30 min In vivo, mast cell-overshoot mice exhibited a trend of reduced inflammation, together with increased peritoneal resolvin D1 release. Conclusions: Mast cells can actively contribute to resolution of allergic inflammation by releasing resolvin D1.